Nilai Karakter Siswa dalam Kompetisi Inovasi Permainan Tradisional Engkle - Avinindy Inayda Devianti; Ujang Jamaludin (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Nowadays, we cannot deny that traditional games have begun to disappear, eroded by the times and replaced by the entry of foreign cultures into Indonesia. In the current millennial era, at the age of children, rarely does anyone know about traditional games where at the age they play is their world. There are many things that we can get when we play traditional games starting from the benefits of personal development and social development. One of the traditional games in Indonesia is the crank game. Before the rise of foreign culture in Indonesia, children at elementary school age, in particular, would play traditional games during recess. This is one of the main issues related to whether student character values can be instilled through the implementation of traditional games, especially anklets. So that this research will explain that there are student character values that we can build in traditional anklet games which are innovated in learning competitions. This research uses a descriptive qualitative method that describes findings in the field related to the discussion raised, then data will be collected using ethnographic principles, namely observation, interviews, documentation, and field notes. The population in this research is using a saturated population involving all 20 grade II students at SDN Sempu 1 Serang. The results obtained in this study are that the implementation of the traditional ankle game for elementary school students can actually foster student character values related to honest, never giving up, responsibility, and teamwork cohesiveness. So that researchers highly recommend traditional games to be an alternative in teaching practice in an effort to instill student character values as an effort to pass on the cultural values of the Indonesian nation to the nation's next generation.